THE ROLE OF CLOUD COMPUTING IN DRIVING EFFICIENCY AND INNOVATION IN THE ERA OF ECONOMY 5.0 - Zulvia Trinova; Haruni Ode; Hari Susanto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Cloud computing plays a vital role in improving operational efficiency and driving innovation in the era of Economy 5.0. With its ability to store, manage and access data in real-time, cloud computing helps companies reduce information technology infrastructure costs and simplify data management. Companies can easily adjust resources as needed without wasting costs. In addition, cloud computing provides a variety of tools and services that enable experimentation with new technologies, accelerate product and service development, and increase responsiveness to market changes. In the era of Economy 5.0, where technology and humans collaborate to achieve economic and social goals, cloud computing integrates advanced technologies such as artificial intelligence (AI) and the Internet of Things (IoT), creating innovative solutions that improve customer experience, productivity, and new business models. Overall, cloud computing is proving to be a key enabler in the advancement and transformation of the modern economy.